Suppressing APOE4-induced neural pathologies by targeting the VHL–HIF axis - Wei I. Jiang; Yiming Cao; Yue Xue; Yichun Ji; Benjamin Y. Winer; Rashmi Chandra; Xingyuan Fischer Zhang; Mengqi Zhang; Neel S. Singhal; Jonathan T. Pierce; Song Chen; Dengke K. Ma (Proceedings of the National Academy of Sciences, 2025)
The ε4 variant of human apolipoprotein E ( APOE4 ) is a key genetic risk factor for neurodegeneration in Alzheimer’s disease and elevated all-cause mortality in humans. Understanding the factors and mechanisms that can mitigate the harmful effects of APOE4 has significant implications. In this study, we find that inactivating the VHL-1 (Von Hippel–Lindau) protein can suppress mortality, neural and behavioral pathologies caused by transgenic human APOE4 in Caenorhabditis elegans . The protective effects of VHL-1 deletion are recapitulated by stabilized HIF-1 (hypoxia-inducible factor), a transcription factor degraded by VHL-1. HIF-1 activates a genetic program that safeguards against mitochondrial dysfunction, oxidative stress, proteostasis imbalance, and endolysosomal rupture—critical cellular events linked to neural pathologies and mortality. Furthermore, genetic inhibition of Vhl reduces cerebral vascular injury and synaptic lesions in APOE4 mice, suggesting an evolutionarily conserved mechanism. Thus, we identify the VHL–HIF axis as a potent modulator of APOE4 -induced neural pathologies and propose that targeting this pathway in nonproliferative tissues may curb cellular damage, protect against neurodegeneration, and reduce tissue injuries and mortality.